A study on the possibility to process dense 60NiTi from elementally blended Ni and Ti powders. (October 2021) - Khanlari, Khashayar; Shi, Qi; Hu, Ke; Yan, Zhiqiao; Kelly, Piaras; Cao, Peng; Liu, Xin
Abstract: This research aimed to process 60NiTi with a dense and homogeneous microstructure from a Ni–Ti powder mixture. It was noted that the optimum route, amongst the ones studied in this research, for obtaining parts having a homogeneous microstructure and the highest amount of relative density is as follows: The powder mixture being initially CIPed was sintered at 750 °C for a holding time of 8 h. To homogenize the microstructure and to obtain the required phases, a secondary sintering treatment was applied on samples cut from elementary sintered parts. After conducting this treatment at 1050 °C for 4 h, the formation of a homogeneous microstructure containing mainly NiTi, Ni3 Ti and Ni3 Ti2 phases was observed in the samples. However, the microstructures of these treated samples consisted of ∼34% porosity. Applying HIP treatments, under 180 MPa and for a holding time of 1 h, at different temperatures above the melting start temperature of the samples, treated by the secondary sintering procedure, successfully increased the density of parts. 1181 °C was the maximum temperature at which the parts could be treated without losing their dimensional integrity and parts with the highest relative density of ∼92% were obtained. Highlights: A combination of CIP, sintering and HIP techniques were used to process dense 60NiTi. This was done by employing elementally blended Ni and Ti powders. Routes to process parts having different densities and hardness values were developed. As-processed parts with a maximum relative density of ∼92% were manufactured. These parts showed a hardness of ∼67 HRA.